Socialization Of Usaha Soul Improvement through the Role of Waste Banks as UKM For Economic Drivers at The Al Azka Kamila Indonesia Foundation - Wahyu Kuncoro, Aris; Naryoto, Pambuko; Kristanto, Dwi; Hendrawan, Koen; Kasmawati, Yuni; Ipmawan, Hasan; Jusmanyah, Muhamad (Perkumpulan Alumni dan Santri Mahyajatul Qurro', 2022)
The waste problem is not only related to landfills, as has been the case so far, because the waste management system involves many parties, including waste producers (such as households, markets, institutions, industries, and others), managers (and contractors), regulators, the informal sector, and communities affected by waste management. Its completion requires the involvement of all relevant parties and various approaches. By looking at the above description, it is important to undertake counseling or socialization about the waste management system